Republic of Poland : Arrangement Under the Flexible Credit Line and Cancellation of the Current Arrangement-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Poland. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Poland's macroeconomic performance was strong during the global crisis, supported by sound economic policies. The previous Flexible Credit Line (FCL) arrangements served the Polish economy well and provided adequate insurance against negative spillover risks. Executive Directors emphasized the need to implement economic policies that preserve macroeconomic stability. Against this background, Directors approved the request for a new two-year arrangement under the FCL, which would provide an essential buffer against a possible increase in risk aversion. The authorities intend to treat the new FCL arrangement as a precautionary instrument.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet